2009
DOI: 10.1029/2008jb006172
|View full text |Cite
|
Sign up to set email alerts
|

Seismic modeling of multidimensional heterogeneity scales of Mallik gas hydrate reservoirs, Northwest Territories of Canada

Abstract: [1] In hydrate-bearing sediments, the velocity and attenuation of compressional and shear waves depend primarily on the spatial distribution of hydrates in the pore space of the subsurface lithologies. Recent characterizations of gas hydrate accumulations based on seismic velocity and attenuation generally assume homogeneous sedimentary layers and neglect effects from large-and small-scale heterogeneities of hydrate-bearing sediments. We present an algorithm, based on stochastic medium theory, to construct het… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 55 publications
0
23
0
Order By: Relevance
“…Stefani and De (2001) analyzed a wide range of vertical and horizontal well logs and observed the same statistical characteristics in reservoir scale well logs as in crustal logs (Goff and Holliger, 1999). Huang et al (2009) demonstrated the applicability of spectral-based simulation method to characterize heterogeneity of hydrate-bearing sediments honoring different correlation coefficients between multiple rock properties inferred from collocated well logs. They constructed petrophysical reservoir models to estimate hydrate volume as well as to simulate elastic seismic wave propagation and thus potentially provided a link between seismic expressions of heterogeneities to volume of hydrate in the pore space of poorly consolidated sediments.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Stefani and De (2001) analyzed a wide range of vertical and horizontal well logs and observed the same statistical characteristics in reservoir scale well logs as in crustal logs (Goff and Holliger, 1999). Huang et al (2009) demonstrated the applicability of spectral-based simulation method to characterize heterogeneity of hydrate-bearing sediments honoring different correlation coefficients between multiple rock properties inferred from collocated well logs. They constructed petrophysical reservoir models to estimate hydrate volume as well as to simulate elastic seismic wave propagation and thus potentially provided a link between seismic expressions of heterogeneities to volume of hydrate in the pore space of poorly consolidated sediments.…”
Section: Introductionmentioning
confidence: 94%
“…A significant limitation of their study was that a nonconditional simulation method was employed so that the reservoir models were unable to represent the spatial variability of field observations and measurements. In this study, we extend the nonconditional simulation method used in Huang et al (2009) to a conditional simulation method. Chilès and Delfiner (1999) describe a variety of conditional simulation methods of continuous random functions that have been developed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In hydrate-bearing sediments, gas hydrates can be (a) free-floating in the sediment matrix, (b) contacting and existing sediment grains, but not cementing or (c) cementing and stiffening the bulk sediments [2,3]. The porous microstructure of gas hydrates governs the mechanical strength and hydraulic permeability of the hydrate-bearing sediments [4]. Moreover, for exploration of gas hydrates, the velocity and attenuation of compressional and shear waves depend primarily on the spatial distribution of hydrates in the pore space in sediments [5].…”
mentioning
confidence: 99%
“…The microstructure of hydrates in the pore space of the sediment determines the velocity and attenuation of compression and shear waves, which are the important parameters of hydrate exploration. Moreover the microstructure of the hydrates in sediment is crucial in the field of exploitation, because it governs the mechanical strength and hydraulic permeability of the hydrate-bearing sediment [9].…”
Section: Introductionmentioning
confidence: 99%